Exploring Data and Metrics of Value at the Intersection of Health Care and Transportation: Proceedings of a Workshop - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Evidence from the public health sector demonstrates that health care is only one of the determinants of health, which also include genes, behavior, social factors, and the built environment. These contextual elements are key to understanding why health care organizations are motivated to focus beyond their walls and to consider and respond in unprecedented ways to the social needs of patients, including transportation needs. In June 2016 the National Academies of Sciences, Engineering, and Medicine held a joint workshop to explore partnerships, data, and measurement at the intersection of the health care and transportation sectors. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Transportation and Infrastructure

Pathways to an Equitable and Just Energy Transition: Principles, Best Practices, and Inclusive Stakeholder Engagement: Proceedings of a Workshop - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
While technologies are clearly instrumental in transitioning away from fossil fuel-based energy and toward a decarbonized economy, decisions about which technologies are prioritized, how they are implemented, and the policies that drive these changes will have profound effects on people and communities, with important implications for equity, jobs, environmental and energy justice, health, and more. The National Academies of Sciences, Engineering, and Medicine Committee on Accelerating Decarbonization in the United States: Technology, Policy, and Societal Dimensions was tasked with assessing the broad range of technological, policy, and societal dimensions of decarbonizing the U.S. economy. The committee produced a 2021 report that provides the U.S. government with a roadmap of equitable and robust decarbonization policies. The next report of the committee will address the broader range of policy actors who play a role in equitable energy transition. To inform its deliberations, the committee hosted a 1-day workshop on July 26, 2022 to discuss critical issues of equity and justice during the energy transition. The goal of the workshop, titled Pathways to an Equitable and Just Transition: Principles, Best Practices, and Inclusive Stakeholder Engagement, was to move beyond energy technologies and elicit ideas and insights to inform the development of principles, best practices, and actionable recommendations for a broad range of policy actors and stakeholders in order to fully operationalize equity, justice, and inclusion. This publication summarizes the presentations and discussion of the workshop.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Improving Road Safety in Developing Countries: Opportunities for U.S. Cooperation and Engagement, Workshop Summary -- Special Report 287 - Transportation Research Board; Institute of Medicine; National Research Council (The National Academies Press, 2006)
TRB, the Policy and Global Affairs Division (PGA), and the Institute of Medicine (IOM) have released TRB Special Report 287, Improving Road Safety in Developing Countries: Opportunities for U.S. Cooperation and Engagement. The report summarizes presentations and discussions at a workshop held on January 26-27, 2006, in Washington, D.C. The workshop focused on the sharp increases in road traffic-related deaths and injuries in developing countries with a goal of providing a view of the diversity of U.S. interests, the scope of activities of U.S. agencies addressing this problem, and prospects for further U.S. engagement. The workshop discussions were intended to help the responsible government agencies gauge whether the U.S. response is proportional to the interests at stake and to identify next steps toward a more effective response. PGA and IOM, like TRB, are part of the National Academies, which include the National Academy of Sciences, National Academy of Engineering, Institute of Medicine, and National Research Council.
Keywords: Transportation and Infrastructure

Preventing Teen Motor Crashes: Contributions from the Behavioral and Social Sciences: Workshop Report - Institute of Medicine; Transportation Research Board; National Research Council (The National Academies Press, 2007)
From a public health perspective, motor vehicle crashes are among the most serious problems facing teenagers. Even after more than six months of being licensed to drive alone, teens are two to three times more likely to be in a fatal crash than are the more experienced drivers. Crash rates are significantly higher for male drivers, and young people in the United States are at greater risk of dying or being injured in an automobile than their peers around the world. In fact, in 2003 motor vehicle crashes was the leading cause of death for youth ages 16-20 in the United States. Understanding how and why teen motor vehicle crashes happen is key to developing countermeasures to reduce their number. Applying this understanding to the development of prevention strategies holds significant promise for improving safety but many of these efforts are thwarted by a lack of evidence as to which prevention strategies are most effective. Preventing Teen Motor Crashes presents data from a multidisciplinary group that shared information on emerging technology for studying, monitoring, and controlling driving behavior. The book provides an overview of the factual information that was presented, as well as the insights that emerged about the role researchers can play in reducing and preventing teen motor crashes.
Keywords: Transportation and Infrastructure; Behavioral and Social Sciences; Health and Medicine

Integrating Sustainability into the Transportation Planning Process - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB Conference Proceedings 37: Integrating Sustainability into the Transportation Planning Process summarizes a July 11-13, 2004, conference in Baltimore, Maryland, that examined whether and how sustainability objectives can be introduced into the planning process for surface transportation facilities and operations. The report explores issues associated with sustainability, the vision of a sustainable transportation system, the state of the practice, and strategies for integrating sustainability concepts into transportation planning.
Keywords: Transportation and Infrastructure

Marine Salvage Capabilities: Responding to Terrorist Attacks in U.S. Ports — Actions to Improve Readiness - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB Conference Proceedings 30: Marine Salvage Capabilities: Responding to Terrorist Attacks in U.S. Ports—Actions to Improve Readiness is the report of the TRB Marine Board Workshop on Marine Salvage Response Capability held on August 5-6, 2003, in Washington, DC. The workshop addressed economic, legal, forensic, environmental, and human casualty issues related to salvage. The report contains a summary of workshop discussions and committee recommendations highlighting important topics and issues associated with marine salvage that warrant further, more detailed inquiry by the responsible federal agencies.
Keywords: Transportation and Infrastructure

Offshore Wind Energy Projects: Summary of a Workshop - Transportation Research Board (The National Academies Press, 2011)
TRB Conference Proceedings on the Web 4: Offshore Wind Energy Projects: Summary of a Workshop summarizes a March 2010 workshop held in Washington, D.C., that examined the processes use by the former Minerals Management Service (MMS) for selecting and managing certified verification agents (CVAs) and for identifying appropriate standards for assuring good engineering judgment and practice; for reviewing and approving designs, fabrications, and installations; and for determining acceptable qualifications and role for a CVA associated with nonhydrokinetic offshore renewable energy projects.
Keywords: Transportation and Infrastructure

Financing Surface Transportation in the United States: Forging a Sustainable Future—Now! - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Conference Proceedings 48: Financing Surface Transportation in the United States: Forging a Sustainable Future—Now summarizes a May, 2010 conference that focused on developments in innovative funding techniques and options for securing continued revenue to support national infrastructure and mobility needs.Views presented in Conference Proceedings 48 reflect the opinions of the individual participants and are not necessarily the views of all conference participants, the planning committee, TRB, or the National Research Council.
Keywords: Transportation and Infrastructure

Performance Measures to Improve Transportation Systems: Summary of the Second National Conference - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Conference Proceedings 36, Performance Measures to Improve Transportation Systems: Summary of the Second National Conference are the proceedings from a conference held on August 22-24, 2004, in Irvine, California. The purpose of the conference was to explore the implementation and use of performance measures and to discuss how to monitor the impact of performance measures on the delivery and quality of transportation services. The proceedings include summaries of presentations made in each conference session and of resource papers. These summaries highlight a variety of agencies' experiences with the use of performance measures and identify research that could improve the use of performance measures. The resource papers prepared for the conference are also included in the proceedings.
Keywords: Transportation and Infrastructure

Hazard and Security Plan Workshop: Instructor Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB's Transit Cooperative Research Program (TCRP) Report 86: Public Transportation Security, Volume 10 -- Hazard and Security Plan Workshop: Instructor Guide is designed to assist rural, small urban, and community-based passenger transportation agencies in creating hazard and security plans or in evaluating and modifying existing plans, policies, and procedures consistent with the National Incident Management System.Appendices to the report (which are shipped on a CD bound into the printed report) are linked to below.Appendix A: Lession PlanAppendix B: Instructor PowerPoint Slides and NotesAppendix C: Agenda for ParticipantsAppendix D: Somewhere County Map for WorkshopAppendix E: Guide for Workshop ParticipantsAppendix F: The HSPAppendix G: The HSP Template InstructionsAppendix H: Evaluation FormThe TCRP Report 86: Public Transportation Security series assembles relevant information into single, concise volumes, each pertaining to a specific security problem and closely related issues. These volumes focus on the concerns that transit agencies are addressing when developing programs in response to the terrorist attacks of September 11, 2001, and the anthrax attacks that followed. Future volumes of the report will be issued as they are completed.
Keywords: Transportation and Infrastructure

Transportation Finance: Meeting the Funding Challenge Today, Shaping Policies for Tomorrow - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB Conference Proceeding 33--Transportation Finance: Meeting the Funding Challenge Today, Shaping Policies for Tomorrow summarizes the Third National Conference on Transportation Finance, held October 2002 in Chicago, Illinois and includes committee findings and recommendations developed largely on the basis of information presented and discussion held at the conference. The conference examined new transportation infrastructure and operations financing mechanisms, their structure, and the benefits and costs of implementing such techniques; and explored the development of additional new funding mechanisms and sources.
Keywords: Transportation and Infrastructure

Building Momentum for Change: Creating a Strategic Forum for Innovation in Highway Infrastructure: Creating a Strategic Forum for Innovation in Highway Infrastructure -- Special Report 249 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 1996)
TRB Special Report 249 - Building Momentum for Change: Creating a Strategic Forum for Innovation in Highway Infrastructure urges the formation of the Strategic Forum for Innovation in Highway Infrastructure, whose central mission would be to identify and effect positive change in the fundamental opportunities and incentives for innovation in products and services for the highway system. This report discusses the mission of the Forum, membership and participation, organization and support, related initiatives, steps to launch the Forum, and issues and opportunities for the Forum.The provision of highway infrastructure in the United States is a joint public- and private-sector enterprise. The nearly 6.5 million km (4 million miles) of freeways, urban arterials, rural routes, and residential streets that cross the country are owned and operated by hundreds of state and local agencies and toll authorities that purchase highway products and services from thousands of construction contractors, equipment makers, suppliers of materials and system components, and numerous other private businesses. After many years of gradually expanding and upgrading this vast highway network, the highway community has been given a new mission: to restore the mature street and highway system to good physical condition and make it perform more reliably, safely, and efficiently at minimum cost and with maximum benefit to taxpayers, the environment, and the traveling public.This mission is especially challenging because it must be achieved under heavy and escalating traffic conditions, on facilities that are aging and often in need of major repair and modernization, and under tightening budgetary constraints. In confronting these new challenges, many highway agencies are recognizing the need for greater flexibility in the way they develop and manage projects. Such flexibility is especially critical to ensuring the inflow of new products and processes. Many highway agencies are seeking to tap deeper into the vast potential of private industry to provide the innovative products and services necessary to meet the growing and changing demands being placed on the highway system.
Keywords: Transportation and Infrastructure

Shipboard Automatic Identification System Displays: Meeting the Needs of Mariners -- Special Report 273 - Transportation Research Board (The National Academies Press, 2003)
TRB Special Report 273 - Shipboard Automatic Identification System Displays: Meeting the Needs of Mariners assesses the state of the art in Automatic Identification System (AIS) display technologies, evaluates current system designs and their capabilities, and reviews the relevant human factors aspects associated with operating these systems.

Innovations in Travel Demand Modeling, Volume 1: Session Summaries - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB Conference Proceedings 42, Innovations in Travel Demand Modeling, Volume 1: Session Summaries summarizes the sessions of a May 21-23, 2006, conference that examined advances in travel demand modeling, explored the opportunities and the challenges associated with the implementation of advanced travel models, and reviewed the skills and training necessary to apply new modeling techniques.
Keywords: Transportation and Infrastructure

International Perspectives on Road Pricing - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB Conference Proceedings 34: International Perspectives on Road Pricing is the proceedings of the International Symposium on Road Pricing held on November 19-22, 2003, in Key Biscayne, Florida. The event was a collaborative effort of TRB, the Florida Department of Transportation, the Organization for Economic Cooperation and Development, and the federal Highway Administration. The report includes two commissioned resource papers that examine the evolution of congestion pricing and the state of the practice in road pricing outside the United States. The proceedings also explore pricing successes and the challenges that have accompanied specific projects’ implementation, as well as the potential evolution of road pricing in the future.
Keywords: Transportation and Infrastructure

Innovations in Travel Demand Modeling, Volume 2: Papers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB Conference Proceedings 42, Innovations in Travel Demand Modeling, Volume 2: Papers includes the papers that were presented at a May 21-23, 2006, conference that examined advances in travel demand modeling, explored the opportunities and the challenges associated with the implementation of advanced travel models, and reviewed the skills and training necessary to apply new modeling techniques. TRB Conference Proceedings 42, Innovations in Travel Demand Modeling, Volume 1: Session Summaries is available online.
Keywords: Transportation and Infrastructure

Sustainable and Resilient Supply Chains Using Emerging Technologies: Policy Options: Proceedings of a Workshop–in Brief - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The coronavirus disease 2019 (COVID-19) crisis sparked concerns about the vulnerability of supply chains and the significant impact of their disruption on the economy and society within the U.S. and abroad. Issues around global supply chains existed before the pandemic but were also greatly aggravated by it. To consider these issues, the Science and Technology for Sustainability program, in collaboration with the Resilient America Program, Transportation Research Board, and Board on Atmospheric Sciences and Climate at the National Academies of Sciences, Engineering, and Medicine, held a series of four virtual workshops on February 3, 4, 17, and 18, 2021. The workshop series addressed opportunities, challenges and environmental implications of increasing local inclusion and community participation in global value chain networks by using new technologies to strengthen resilience and sustainability in the face of recurring disruptions. The series also explored the feasibility of introducing advanced manufacturing, logistics and decision-making under alternative supply chain scenarios in different sectors, with a view to strengthening the resilience of communities and adopting far more environmentally and economically sustainable consumption and production approaches. This publication summarizes the presentations and discussion of the workshops.
Keywords: Environment and Environmental Studies